Teorema de Pitágoras: proposta de sequência didática para o trabalho com demonstrações no 9° ano do ensino fundamental - Gomes, João Lorena de Jesus Gomes (2024)
This work adresses the role and importance of demonstrations in Mathematics classes for the final Years of Elementary Education. To this end, it considers as a starting point the BNCC, which includes the performance of demonstrations among the skills that students should acquire throughou their schooling. It discusses the demonstration as intrinsic characteristic of Mathematics, as a means of validation and advancement in the most diverse fields of study of this Science. It also presents he suggestion of three demonstration of the Pythagorean theorem that can be carried out together with 9th-grade students of Elementary Education, in order to answer the guiding question “How is it possible to perform demonstrations of the Pythagorean theorem in Elementary Education?”.